PENJAMIN MUTU PENDIDIKAN GURU BIMBINGAN KONSELING DALAM MENINGKATKAN MUTU PEMBELAJARAN DI SEKOLAH MENENGAH KEJURUAN (SMK) - Diana Septi Purnama (MAJALAH ILMIAH PEMBELAJARAN, 2011)
In the constellation of global education one of the vital areas of thefield of guidance and counseling. Strategis strata occupy this area as amainstay of the global competitive ability of a country because it isclosely related to human resource development hegemony superiorschools in a variety of scales. Guidance and counseling field related toquality have logical consequences that are very heavy, because it mustwork in both worlds. Campus as a center of education, training,personality development, management ability and communicationskills. On the other hand, graduates/school counselor produced byLPTK to be completely coherent, insight and eligible with the existingschool environment. Based on the thought of two things above thefield of guidance and counseling specifically for teacher educationpattern which should be developed is set multy entry-exit systemmodel. This model puts environmental school as an integral part inthe learning process, so it will act as a technical academic widerlaboratory. And process quality guarantee automatically attacheddirectly to the user that is educational industry itself.